Financial Transfer In Cyber Currency And The Private International Law - Norouzi, Nima (Pusat Kajian Hukum Perbankan Fakultas Hukum Universitas Jember, 2022)
The object of this study is the analysis of the legal nature of the so-called cryptocurrencies or virtual currencies and the positions defended by different authors based on the current regulatory status and the decisions issued by international authorities, with special emphasis on the conception of cryptocurrencies as “means of payment” and “property susceptible of ownership.” In addition, an examination is also carried out on the sufficiency of the existing legal mechanisms in matters of private international law to deal with the consequences derived from said qualifications and on the possibility or need to carry out legislative modifications to achieve a satisfactory regulation of cyber currencies.